The utilization of drama activities in the enhancement of speaking skill - Farooq Ali AlHasan, Lect .Dr. Hind; M. Ridha Abdulhussein Altaie, Assis.Lect . Tawadud (Basra studies journal, 2023)
Drama has now become pedagogy with a pretty full component that combines including mind, body, feelings, as well as emotions to develop personalized interactions with real-life events for pupils to be engaged mostly in language acquisition. This study will investigate the benefits and drawbacks of incorporating drama into the learning and teaching of the language. The new drama is already suggested as an efficient approach for developing pupils' speaking abilities in teaching English. Drama, in general, delivers additional benefits, not just in terms of pupils' speaking skills, and in many other domains. Furthermore, various issues could develop throughout the high school drama language instruction approach. This study gives a critical examination of multiple empirical studies regarding drama techniques that have been used in the context of foreign language acquisition via cross-checking and then examining eclectically using various sources. Mostly to generalize, drama has always been undoubtedly valuable in language acquisition. However, various issues in its execution must be addressed in order to adequately meet educational targets. According to the evaluation results, several challenges that may arise during the application of drama are uncontrolled time management, the disorganized environment, the use of the original language, as well as status within schools. So this study aims at determining the impact of Drama Activities on EFL preparing students' performance in order to improve their speaking skills; and determining the influence of Drama Activities in enhancing EFL preparing students' post-test performance at comprehension and production levels. Two groups of students were chosen for the study each of 30 students, an experimental which is taught by using drama activities and the control one which is taught by the traditional method; and it was found statistically that the performance of the first group is better than the second one.